On Growth of Free Burnside Groups - Bayramyan, Arman (Armenian Journal of Mathematics, 2025)
In his seminal monograph, S. I. Adian established a lower bound on the growth of the free Burnside group B(2,n) for odd n≥ 665. Building on Adian’s methods, we extend this result to free Burnside groups B(m,n) of arbitrary rank m≥ 2. As a consequence, we obtain growth estimates for a broad class of finitely generated groups.